Analysis of Green Marketing Tools towards Consumer Purchase Intention in Kathmandu - Shrestha, Shulov (Journal of Business and Social Sciences Research, 2018)
The main purpose of this study is to examine the impact of green marketing tools on product choice and how green initiatives influence purchase intention of consumers. The research also attempts to examine the relationship between age, income, education, and occupation with consumer purchase intention in association with green marketing tools. The study is descriptive in nature and focuses on hypothesis testing using structured questionnaire and interview. Structured questionnaire is used to collect primary data from a sample size of 120 respondents focusing on employed, self-employed, students and homemakers. These groups are assumed to represent green purchase in today’s society. However, opinions of marketing professionals have also been considered. The survey population represents the people who go for shopping; data have also been collected from the point of purchase. Green purchase intention was seen to be incremental considering the increase in the level of education of individuals. Green marketing tools i.e., environmental belief, green packaging, green branding, green advertisement, green labelling has been taken into account to observe its significance towards consumer purchase intention. Likert scale questions with five-scalerating were used to do the hypothesis testing. The questions included statements in conjunction with the measure of green marketing tool’s influence over consumer purchase intention. The research revealed that green marketing tools played a significant role in inducing a positive purchase intention towards green products. While there exists growing preference towards green products, price plays a major role in product purchase. Journal of Business and Social Sciences Research, Vol. 1, Issue 1, pp. 37-57